Wet Load Study of Gross Pollutant Traps; Kemensah River, Malaysia. Issue 1 (March 2016) - Zahari, N. M.; Sidek, L. M.; Basri, H.; Md Said, N. F.; Md Noor, M. S. F.; Jajarmizadeh, M.; Zainal Abidin, M. R.; Mohd. Dom, N.
Abstract: Efforts have been made by the government agency to install the Gross Pollutant Trap (GPT) to protect of entering the gross pollutants from direct discharge into the river. Few studies have been performed in related to GPT and there is a need to do research on the performance of GPTs in Malaysia. The performance of GPTs is strongly dependent on installed location. Moreover, contribution of landuse has also potential to evaluate the GPTs performance. The main objective of this paper is to analyse the wet load that has been trapped inside GPTs. In this study, Installation of GPTs are performed based continuous deflective separation (CDS) and downstream defender (DD). Kemensah River is chosen as a case study and GPTs are installed at drainage systems due to analysis the impact of GPTs on reduction of solid waste from discharge to the Kemensah River. The result shows that the GPTs can reduce the gross pollutants before entering the river system in optimum way. Consequently, the area of catchment, dense residential area and rainy season have important role on increasing the gross pollutant.